2006
DOI: 10.1007/s00428-006-0280-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of the NM23 protein in salivary gland neoplasms with distinct biological behavior

Abstract: The NM23 protein was shown to be associated with metastasis suppression in human malignancies with various tissue origins. However, its association with the metastatic phenotype of salivary gland neoplasms (SGN) remains unknown. To evaluate the role of NM23 in SGN, the expression patterns of NM23 in the following were compared: benign (pleomorphic adenoma) vs malignant (adenoid cystic carcinoma and mucoepidermoid carcinoma) SGN, and primary malignancies with/without evidence of metastasis vs their metastatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…Our results are similar to those of Göhring et al 22 in their 2002 paper, where nm23-h1 protein positivity was unrelated to metastatic breast carcinomas. On the other hand, our results disagree with those of Nascimento et al, 23 who investigated benign and malignant salivary gland neoplasms and found that the presence of the nm23 protein in the nucleus may be a good indicator for predicting the metastatic potential of salivary gland malignancies.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are similar to those of Göhring et al 22 in their 2002 paper, where nm23-h1 protein positivity was unrelated to metastatic breast carcinomas. On the other hand, our results disagree with those of Nascimento et al, 23 who investigated benign and malignant salivary gland neoplasms and found that the presence of the nm23 protein in the nucleus may be a good indicator for predicting the metastatic potential of salivary gland malignancies.…”
Section: Discussioncontrasting
confidence: 99%
“…Both reduced expression and overexpression of NM23 have been demonstrated to correlate with increased metastasis and poorer prognosis in cancers from different sites 12 . Cytoplasmic NM23 staining can be demonstrated in the majority of pleomorphic adenomas, adenoid cystic carcinomas and mucoepidermoid carcinomas, with no significant difference in the frequency of positive cells among these tumours 13 . However, nuclear expression of NM23 is restricted to malignant salivary gland tumours with metastasis 13 .…”
Section: What Is New In Immunohistochemistry?mentioning
confidence: 99%
“…12 Cytoplasmic NM23 staining can be demonstrated in the majority of pleomorphic adenomas, adenoid cystic carcinomas and mucoepidermoid carcinomas, with no significant difference in the frequency of positive cells among these tumours. 13 However, nuclear expression of NM23 is restricted to malignant salivary gland tumours with metastasis. 13 Hence, nuclear NM23 staining may be used for predicting metastasis in salivary gland carcinomas.…”
Section: Markers For Luminal Cellsmentioning
confidence: 99%
See 1 more Smart Citation